Numerical study of seismic earth pressures acting against a vertical retaining wall in frictional soil - Zerguine, Salah; Benmeddour, Djamel; Zatar, Abdallah (Journal of Applied Engineering Science & Technology, 2016)
The seismic earth pressures with presence of water, acting against a vertical retaining wall are often a function of many parameters. In the case of saturated sands, the earthquake causes failure of the retaining wall resulting by soil liquefaction. The theoretical methods for the calculation of seismic earth pressures available in literature remain unable to solve the envisaged problems. In this study the finite element code PLAXIS is used to evaluate the active earth pressure acting against a vertical rigid retaining wall. The soil is modeled by an elasto-plastic model with a Mohr-Coulomb yield criterion.  In this study, several parameters have been considered in order to evaluate the effect of soil acceleration with transitory flow and hydrostatic groundwater. The results have been compared with those obtained by the pseudo-dynamic and pseudo-static approaches. The results show the influence of the seismic action on the earth pressures.
Keywords: Retaining wall; Frictional soil; Seismic earth pressure; Finite element; PLAXIS